ANALISIS APRAISAL CITRA JOKO WIDODO PADA HARIAN KOMPAS PADA PEMILIHAN PRESIDEN 2014 - ARSEN NAHUM PASARIBU (LP2MTBM MAKARIOZ, 2019)
The study aims to reveal how the image of Joko Widodo, one of the presidential candidates, was formed and presented in the Kompas Daily Newspaper during the 2014 presidential election campaign. This research is descriptive qualitative in the form of Joko Widodo's image depicted by Evaluation Theory (TE), or commonly known as Appraisal Analysis (AA) developed by Martin & White (2005) based on Halliday (1994) Systemic Functional Linguistics (SFL) Theory. The corpus data of this study consisted of 100 main headlines of the Kompas Daily Newspaper taken during the campaign period of the official presidential election in 2014. This finding revealed that the Kompas Daily Newspaper predominantly portrayed Joko Widodo positively and reported little of Joko Widodo's negative image